Application of a numerical index of discriminatory power to a comparison of four physiochemical typing methods for Candida albicans. - Hunter, P R (1989)
Four typing methods for the strain differentiation of Candida albicans (morphotyping, resistotyping, extracellular enzyme production, and carbon source assimilation reactions) were compared on a single population of 100 strains. An index of discriminatory power was used to facilitate this comparison. Extracellular enzyme production had poor discriminatory power, and carbon source assimilation reactions were poorly reproducible. Morphotyping and resistotyping had acceptable reproducibility and discrimination. The use of resistotyping and morphotyping in parallel enhanced discrimination without an unacceptable decrease in reproducibility, although other combinations did not enhance discrimination because reproductibility was impaired.